Methodical approach for determination of the heterocyclic aromatic amines in meat products using HPLC–MS/MS - D. A. Utyanov; A. V. Kulikovskii; A. S. Knyazeva; A. A. Kurzova; A. N. Ivankin (Теория и практика переработки мяса)
Heterocyclic aromatic amines (HAA) are formed in foods of animal origin during the Maillard reaction due to the high creatine and creatinine contents. HAA have carcinogenic and mutagenic effects. HAA content is not standardized in the Russian Federation and the Customs Union territory. However, in the EU countries, comprehensive monitoring studies are carried out on the HAA contents and effect on the human body. Due to constant expansion of the list of controlled contaminants in food products, analytical laboratories need to develop methods for determining HAA in food items. As a result of the research, a method for HAA determination was developed using high-performance liquid chromatography with mass spectrometry in the mode of specified reaction monitoring. Comparative tests of the two methods for sample preparation were carried out. The advantages and disadvantages of sample preparation approaches were substantiated. The existing SPE conditions were optimized, which made it possible to concentrate trace amounts of MeIQx and PhIP and to dispose of substances suppressing analyte ionization. The estimation of method accuracy and specificity was carried out. The degree of ionization suppression by the matrix for MeIQx and PhIP analytes was determined. The degree of HAA extraction was empirically established. For biological samples of animal origin, it was up to 90.9% for MeIQx and up to 89.4% for PhIP. It is shown that, in accordance with the developed methodology, HAA may be determined with an accuracy of 96.15 to 98.4% at the levels of 5 to 20 ng/g. The limit of quantification of the target substances was 3 ng/g.